The Effect of Circuit Learning on Improving The Physical Fitness of Elementary School Students - Jariono, Gatot; Nugroho, Haris; Hermawan, Iwan; Fachrezzy, Fahmy; Maslikah, Uzizatun (CV. Inara, 2021)
The purpose of this study is to determine the influence of circuit learning on improving the physical fitness of elementary school students. This research was conducted at SDN 135 Sajoanging Wajo Regency of South Sulawesi Province, with a sample of 20 people. The method used in this study is to use asi experiments. The data analysis technique used in this study is to use descriptive analysis and inference analysis, descriptive analysis is used to describe the results of this study while inference analysis uses uji_t with a significant degree α=0.05 analysis used with the help of SPSS version 20.0. The results of this study found that circuit learning had a significant influence on improving the physical fitness of elementary school students. Thus, it can be concluded that circuit learning is one of the alternatives to improving the physical fitness of school students.